Desenhos sobre aprendizagem e não aprendizagem: a construção do conhecimento social sob o enfoque piagetiano - Saravali, Eliane Giachetto [UNESP]; Guimarães, Karina Perez; Guimarães, Taislene; Melchiori, Ana Paula (My University, 2012)
The article presents preliminary data of a survey that aimed to investigate the beliefs of children and adolescents about not learning. A total of 80 students, aged 6 to 16 years participated of the study. Among the participants, 20 are 6 years old, 20 are 9, 20 are 12 and 20 are 16 years old. As methodological tool, it was asked the participants to draw a person that learns and another one that doesn’t learn. Data was analyzed according to the Piagetian perspective for the construction of social knowledge. The main results indicate that a significant part of the participants tend to blame the students for the result of no learning. This indicates that students are able to consider the amplitude of different dimensions of social phenomena only partially. When considering the level of understanding of social reality, it was observed that, even at older ages, participants have a very basic notion of the social world.

O artigo apresenta dados parciais de uma pesquisa que objetivou investigar as crenças de crianças e adolescentes sobre o não aprender. Participaram do estudo 80 escolares entre 6 e 16 anos, sendo 20 de 6, 20 de 9, 20 de 12 e 20 de 16 anos. O instrumento metodológico apresentado aqui é a solicitação de um desenho em que os sujeitos deveriam desenhar uma pessoa que aprende e uma que não aprende. Os dados foram analisados de acordo com a perspectiva piagetiana para a construção do conhecimento social. Os principais resultados obtidos indicam que grande parte dos sujeitos tende a culpabilizar o aluno pela não aprendizagem, revelando dificuldades em considerar a amplitude e as diferentes dimensões dos fenômenos sociais. Em relação aos níveis de compreensão da realidade social, observou-se que, mesmo em idades mais avançadas, os sujeitos permanecem com noções bastante elementares sobre o mundo social.
Drawings of learning and not learning: the construction of social knowledge under the piagetian approach